2004
DOI: 10.1097/00001432-200412000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the treatment of infections due to resistant Staphylococcus aureus

Abstract: The promising data that have emerged in the last year indicate that we may have six available drugs to treat resistant S. aureus infections within the next few years. The next goal is to determine the appropriate indications and cost-effectiveness of each of these drugs in our treatment strategy against S. aureus and other Gram-positive pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Many new compounds with activity against MRSA are under development but few have been licensed [43,44]. Drugs of potential interest for severe MRSA pulmonary infections, including VISA and VRSA strains, are tigecycline, a member of the glycylcycline group of antibiotics (which are tetracycline analogues), ceftobiprole, a novel broadspectrum parenteral cephalosporin, and telavancin, a novel lipoglycopeptide, all currently on trial in patients with NP.…”
Section: New Therapeutic Options For Mrsa Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Many new compounds with activity against MRSA are under development but few have been licensed [43,44]. Drugs of potential interest for severe MRSA pulmonary infections, including VISA and VRSA strains, are tigecycline, a member of the glycylcycline group of antibiotics (which are tetracycline analogues), ceftobiprole, a novel broadspectrum parenteral cephalosporin, and telavancin, a novel lipoglycopeptide, all currently on trial in patients with NP.…”
Section: New Therapeutic Options For Mrsa Pneumoniamentioning
confidence: 99%
“…However, the cyclic lipopeptide daptomycin cannot be recommended for MRSA pneumonia because of its poor penetration into pulmonary tissue. Binding of the drug by surfactant is probably responsible for the low levels reached in the bronchial alveolar lining fluid and lung parenchyma [43][44][45]. In a recent prospective trial of 740 patients with pneumonia, daptomycin was found to be less effective than the comparator ceftriaxone, thereby causing early discontinuance of the study [43].…”
Section: New Therapeutic Options For Mrsa Pneumoniamentioning
confidence: 99%
“…Telavancin, linezolid, daptomycin, tigecycline, and quinupristin-dalfopristin can be used for vancomycin-intermediate S. aureus (VISA). For VRSA strains testing should be performed (96,97). Oritavancin, dalbavancin, ceftobiprole, and ceftaroline are newer agents under development for treatment of resistant strains (97).…”
Section: Treatmentmentioning
confidence: 99%
“…In the late 1980s a second glycopeptide, teicoplanin (a similar agent to vancomycin), was introduced in Europe. In the new millennium a number of new antimicrobial agents were introduced with activity against MRSA: linezolid, daptomycin and tigecycline [7][8][9][10][11] . Two new lipoglycopeptides (i.e.…”
Section: Introductionmentioning
confidence: 99%